2010
DOI: 10.1111/j.1600-065x.2010.00925.x
|View full text |Cite
|
Sign up to set email alerts
|

Measles virus‐induced suppression of immune responses

Abstract: Summary Measles is an important cause of child mortality that has a seemingly paradoxical interaction with the immune system. In most individuals, the immune response is successful in eventually clearing measles virus (MV) infection and in establishing life-long immunity. However, infection is also associated with persistence of viral RNA and several weeks of immune suppression, including loss of delayed type hypersensitivity responses and increased susceptibility to secondary infections. The initial T-cell re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

4
136
0
10

Year Published

2010
2010
2024
2024

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 160 publications
(150 citation statements)
references
References 204 publications
(306 reference statements)
4
136
0
10
Order By: Relevance
“…The propensity of HCV to infect the immune system is consistent with a significantly greater prevalence of lymphoproliferative disorders, such as non-Hodgkin's lymphoma and mixed cryoglobulinemia, and perhaps mucosa-associated lymphoid tissue lymphoma, in patients infected with HCV (4,10,13,40,42). It also is possible that HCV residing in immune cells, like other persistent viral infections (5,14,26,29), is an important contributor to longterm virus persistence and that the infected immune cells are reservoirs from which infection can spread, for example, in patients grafted with new livers due to HCV-related end-stage disease or in recipients of seemingly HCV-negative donor organs (24,25,39).…”
mentioning
confidence: 89%
“…The propensity of HCV to infect the immune system is consistent with a significantly greater prevalence of lymphoproliferative disorders, such as non-Hodgkin's lymphoma and mixed cryoglobulinemia, and perhaps mucosa-associated lymphoid tissue lymphoma, in patients infected with HCV (4,10,13,40,42). It also is possible that HCV residing in immune cells, like other persistent viral infections (5,14,26,29), is an important contributor to longterm virus persistence and that the infected immune cells are reservoirs from which infection can spread, for example, in patients grafted with new livers due to HCV-related end-stage disease or in recipients of seemingly HCV-negative donor organs (24,25,39).…”
mentioning
confidence: 89%
“…Clinical disease associated with infection by several paramyxoviruses such as mumps virus or measles virus (MeV) originate predominantly from immunopathogenic effects, which makes therapeutic treatment challenging, because viral replication is typically immune-controlled and titers decline when symptoms become manifest (14,15). In the case of RSV infection, however, several studies have suggested that pathogenesis is not the result of host immunopathology alone.…”
mentioning
confidence: 99%
“…MV infects primarily hematopoietic and epithelial cells and causes a severe transient immune suppression facilitating secondary infections that is due to interference with both innate and adaptive immune responses, including the type I IFN network (20,23,38,39,61).…”
mentioning
confidence: 99%